Pengaruh Pemendaman Basis Gigi Tiruan Resin Akrilik Polimerisasi Panas dalam Minuman Tuak Aren Terhadap Kekasaran Permukaan dan KekuatanIimpak - Dwi Tjahyaning Putranti; Lidya Pratiwi Ulibasa (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2015)
Tuak aren is traditional alcoholic beverages from North Sumatera especially consumed by Bataknese and Simalungunese. Some of those people are the heat cured acrylic denture wearers. This purpose of this research is to study the effect of immersion duration of heat cured acrylic resin in “Tuak aren” towards surface roughness and impact strength. The samples are heat cured acrylic resin plate with a size of 65 x 10 x 2,5 mm for testing the surface roughness and 80 x 10 x 4 mm for testing the impact strength. There are total 12 groups, 6 groups for surface roughness test and 6 groups for impact strength test. Each group consists of 6 samples. Either treatment sample (“Tuak aren”) and control sample (aquadest) were immersed for 5, 10 and 15 days. Based on T-Independent test, there were significant differences of surface roughness (∆Ra) and impact strength of heat cured acrylic resin between after being immersed in “Tuak aren” and in aquadest for 5, 10, and 15 days. Then, based on One-Way Anova test, the result showed various immersion duration have no significant influenced on surface roughness (∆Ra) (p > 0,05) but various immersion duration have significant influenced on impact strength (p < 0,05). Heat cured acrylic resin denture base exposed to “Tuak aren” for three years can decrease its impact strength nevertheless the changes of surface roughness doesn’t occur significantly.